Statistical comparison of global solar radiation estimation models over Turkey - Demirhan, Haydar; Menteş, Turhan; Atilla, Mustafa (Energy conversion and management, 2013)
► Accuracy of solar radiation estimation models is compared over Turkey. ► Use of statistical model comparison approaches is introduced in solar energy. ► The TEKNOLOGIS model is found superior to the GEPA and METEONORM models. ► Use of the TEKNOLOGIS model highly ensures effective use of resources for Turkey. Production of energy from clean and renewable resources is an appealing subject nowadays. Solar energy has an important place among the renewable energy resources. METEONORM, TEKNOLOGIS and GEPA are models used to estimate the amount of global solar radiation recorded over the surface of Earth particularly over the region of Turkey. In this work, we compare and evaluate these models in terms of accuracy of estimation. As a result, the TEKNOLOGIS model is found to be superior to the other models in terms of preciseness in the estimation of the amount of horizontal global solar radiation reaching at a particular point over the region of Turkey.